2016
DOI: 10.1039/c5dt03366g
|View full text |Cite
|
Sign up to set email alerts
|

Selective hydrogenation of levulinic acid to γ-valerolactone using in situ generated ruthenium nanoparticles derived from Ru–NHC complexes

Abstract: Hydrogenation of levulinic acid (LA) to γ-valerolactone (GVL) was studied by using mono- and bidentate p-cymene ruthenium(ii) N-heterocyclic carbene (NHC) complexes as catalyst precursors. In water, all complexes were found to be reduced in situ to form ruthenium nanoparticles (RuNPs) with a high hydrogenation activity. In organic solvents, complexes with monodentate NHC ligands also formed nanoparticles, while complexes with bidentate ligands gave rise to stable homogeneous catalysts with moderate hydrogenati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…In complex 3a , three singlet signals at δ = 7.54, 7.16, and 6.36 ppm were observed due to the imidazolylidene backbone and pyrazole CH protons, whereas two doublets at δ = 5.31 and 4.96 ppm were assigned to the methylene protons. The p ‐cymene signals of 3a resonated at δ = 5.34–5.86 ppm, which was similar to those of the known NHC–Ru–( p ‐cymene) complexes depending on the ancillary ligands . In addition, the 13 C NMR spectrum of 3a exhibited carbenic carbon resonances at δ = 173.8 ppm, which is typical of a ruthenium–carbene complex.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…In complex 3a , three singlet signals at δ = 7.54, 7.16, and 6.36 ppm were observed due to the imidazolylidene backbone and pyrazole CH protons, whereas two doublets at δ = 5.31 and 4.96 ppm were assigned to the methylene protons. The p ‐cymene signals of 3a resonated at δ = 5.34–5.86 ppm, which was similar to those of the known NHC–Ru–( p ‐cymene) complexes depending on the ancillary ligands . In addition, the 13 C NMR spectrum of 3a exhibited carbenic carbon resonances at δ = 173.8 ppm, which is typical of a ruthenium–carbene complex.…”
Section: Resultssupporting
confidence: 63%
“…In addition to displaying promising biological activity, the Ru–NHC complexes 3a and 3b presented here contained a strong Ru–carbene bond and reversible decoordination and coordination nitrogen heterocyclic group; therefore, we envisaged that they should be good catalyst candidates ,. [12b] The catalytic activity of 3a and 3b for the oxidation of alcohol derivatives was thus investigated. To optimize the reaction conditions, benzyl alcohol was first selected as a model substrate to evaluate the catalytic activity of complexes 3a and 3b .…”
Section: Resultsmentioning
confidence: 99%
“…Using RuNPs in organic solvents such as THF, the catalytic activities were lower with those obtained in water, and in the presence of alcohols such as methanol and propanol the main products were their corresponding levulinate esters. Tay et al (2016) investigated hydrogenation reaction of LA to GVL catalyzed by water-dispersible RuNPs obtained in situ from both monodentate and bidentate p-cymene ruthenium(II) N-heterocyclic carbene (RuNHC) complexes as catalyst precursors in aqueous media. p-cymene RuNHC catalyst precursors with monodentate Nheterocyclic carbene ligands form RuNPS in both water and organic solvents and exhibited much higher catalytic activities in water (TOF = 361 h −1 ) compared with those obtained in organic solvents such as THF (TOF= 3 h −1 ), methanol, and isopropanol (Table 1).…”
Section: Heterogeneous Water-dispersible Catalytic Nanoparticlesmentioning
confidence: 99%
“…Moreover, the transesterification is a fast reaction if compared with the hydrogenation step. The impact of catalyst content on the hydrogenation showed that the increase in catalyst loading level dramatically promoted GVL yield as well as GVL selectivity ( Table 3 , runs [11][12][13][14][15], indicating a positive contribution on the availability of the catalytic sites. Finally, the effect of initial hydrogen pressure to the hydrogenation suggested that an increase of hydrogen pressure between 1.0 and 4.0 MPa significantly enhanced both GVL yield and selectivity, although the hydrogen pressure showed very limited effect on EL conversion ( Table 3 , runs [16][17][18][19] under the investigated conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Homogeneous catalysts generally show a high catalytic efficiency under mild reaction conditions due to their excellent accessibility leading to a full contact with the substrate molecules. Various transition metal-based catalysts such as Ir [3] , Pd [4] , Fe [5] , Zr [6] were reported for GVL preparation, but Ru-based homogeneous catalysts were extensively investigated for this transformation, which include Ru(CO) 4 I 2 [7] , RuCl 2 (PPh 3 ) 3 [8] , RuHCl(CO)(PPh 3 ) 3 [9] , Ru Ⅱ -BINAP-HCl (BINAP = 2,2 -bis(diphenylphosphino) −1,1binaphthyl) [10] , Ru(acac) 3 /PBu 3 (acac = acetylacetone) [11] , Ru 4 (Cl) 8 ( p -cymene) 4 (L1) 4 Zn 2 [L1 = 4-(diphenylphosphino)benzoic acid] [12] , Ru-(TPPTS) (TPPTS = tris(3-sulfonatophenyl)phosphine, sodium salt) [13] , and Ru-NHC (NHC = N -heterocyclic carbenes) [14] . However, many limitations from complex and expensive ligands, high cost of precious transition metals as active sites, and unrecyclable nature had seriously restricted their applications in LA(EL)-to-GVL transformations in industrial scales.…”
Section: Introductionmentioning
confidence: 99%